BeeBox: A novel artificial nestbox for bumblebee research, conservation and engagement - Philip Donkersley; Jenny Roberts (Methods in Ecology and Evolution)
Abstract Pollinators, particularly bumblebees, play a vital role in global food production, yet their populations face severe declines due to habitat loss. While conservation efforts have focused on food provision, the critical need for suitable nesting habitats has been largely overlooked. We present a novel artificial nestbox, the BeeBox, designed to support bumblebee nesting and enhance research, conservation and public engagement. Developed using additive manufacturing (AM) principles, the BeeBox underwent iterative design improvements to optimize thermal insulation, humidity control and durability. Field tests demonstrated that our design significantly improved internal environmental stability, colony health and longevity. The modular design facilitates in‐nest behavioural studies using high‐resolution video recording, providing a robust tool for understanding the impacts of environmental stressors. Additionally, the BeeBox offers scalable, cost‐effective conservation applications, with the potential to supplement declining natural habitats. Observations indicate that post‐occupancy cleaning by detritivores can mitigate pathogen accumulation, enhancing long‐term nestbox utility. BeeBox also serves as a platform for public engagement, with videos of bumblebee behaviour fostering awareness and emotional connections to pollinator conservation. Interactive initiatives, such as personalized nestbox distribution, further inspire community participation. By integrating scientific research, conservation strategies and public outreach, the BeeBox represents a comprehensive approach to addressing bumblebee population declines and promoting biodiversity.